Drug-related genetic polymorphisms affecting severe chemotherapy-induced neutropenia in breast cancer patients: A hospital-based observational study. Issue 44 (November 2016) - Tsuji, Daiki; Ikeda, Midori; Yamamoto, Keisuke; Nakamori, Harumi; Kim, Yong-Il; Kawasaki, Yohei; Otake, Aki; Yokoi, Mari; Inoue, Kazuyuki; Hirai, Keita; Nakamichi, Hidenori; Tokou, Umi; et al.
Abstract : Abstract: Chemotherapy-induced neutropenia (CIN) is one of the major adverse events that necessitate chemotherapy dose reduction. This study aimed to evaluate the association between grade 4 neutropenia and genetic polymorphisms in breast cancer patients. In this genetic polymorphism association study, peripheral blood samples from 100 consecutive breast cancer outpatients, between August 2012 and September 2014, treated with doxorubicin and cyclophosphamide (AC) combination chemotherapy were genotyped for polymorphisms in adenosine triphosphate-binding cassette subfamily B member 1 ( ABCB1 ), cytochrome P450 (CYP) enzyme-coding genes ( CYP2B6 and CYP3A5 ), glutathione S-transferase ( GST ), and excision repair cross-complementing 1 ( ERCC1 ). Associations between grade 4 neutropenia and genotypes as well as risk factors were examined using multivariate logistic regression. From 100 patients, 32.0% had grade 4 neutropenia. Multivariate logistic regression analysis revealed that ERCC1 118C > T (odds ratio [OR], 3.43; 95% confidence interval [CI], 1.22–9.69; P  = 0.020), CYP2B6 *6 (OR, 4.51; 95% CI, 1.21–16.95; P  = 0.025), body mass index (BMI) (OR, 6.94; 95% CI, 1.15–41.67; P  = 0.035), and baseline white blood cell (WBC) count (OR, 2.99; 95% CI, 1.06–8.40; P  = 0.038) were significant predictors of grade 4 neutropenia. ERCC1 and CYP2B6 gene polymorphisms were associated with the extent of grade 4 neutropenia in patients receiving AC chemotherapy. In addition to previously known risk factors, BMI and WBC counts, ERCC1 and CYP2B6 gene polymorphisms were also identified as independent strong predictors of grade 4 neutropenia. Abstract : Supplemental Digital Content is available in the text